Threshold level of weed umbrella sedge (Cyperus iria) in upland rice (Oryza sativa) under rainfed direct-seeded condition - MOORTHY, B T; DAS, T K (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was carried out during the wet season of 1993 and 1994 to find out the minimum density of the problem ,weed umbrella sedge or flatsedge (Cyperus iria L.), which causses the least yield reduction in rainfed direct-seeded upland rice ('Annada'), and above which weed control measures could be contemplated. Different densities of this weed from 40 to 400 plants/m2 producing dry matter of 0.3-2.34 tonnes/ha reduced the grain yield of rice by 11-40%. Thus a density Of 40, plants of Cypems iria/m2 with a dry-matter accumulation of 0.3 tonne/ha could be considered as'the threshold level in upland nee.